Implementation of Green Supply Chain Management Toward Utilization of Palm Oil Waste - Suryani, Bella; Zaqy, Sandi Yudha Barri (Politeknik Negeri Bengkalis, 2024)
Green Supply Chain Management is a supply chain business model that involves an economic and sustainablebusiness practice through environmental-friendly plants. This model is seen to improve the performance of an industry byreducing environmental risks and impacts, efficiency of ecology. Palm oil industry is considered as a big business but hasgenerated a large volume of waste. This research was aimed to discover how to become more sustainable in managing andutilizing the palm oil industry waste. This research used a literature review method and the data is sourced from secondarydata. This research found that the waste of the palm oil industry can promote waste management and convert from an evilto a necessity to maintaining the environment and sustainable economic development.